PENGEMBANGAN INDUSTRI KREATIF PIGURA KALIGRAFI MENUJU PASAR GLOBAL - Zuliyati Zuliyati (Asian Journal of Innovation and Entrepreneurship, 2015)
The productive potential of small industries is creative industries, the creative industries that focuses on creativity and inovation . One of SMEs that have a major role in the creative industries and should be developed in order to exports and  global market is SMEs that rely on the expertise (hand made), such as crafts jewelry, wood carvings and including Frames Craft Calligraphy. The purpose of this activity is to (1) stimulate the growth of exports Frames Calligraphy Indonesia through the growth of a competitive market, (2) enhance the development of Custom Frames Calligraphy in seizing the export opportunities by improving the quality of products and marketing Frames Calligraphy. The method used is Bintek (Guidance Technology), assistance and reinforcement in the production process. Through this method the production process will be effective and efficient, so as to produce quality products. Results of activities, namely the increase in the value of assets and income Craftsmen Frames Calligraphy, increasing the quantity and quality of marketed Calligraphy Frames, increase the marketing of products and production processes more effective and efficient. Keywords: Export, Calligraphy, Quality, Frames, SMEs